Factors Affecting Teachers Retention in a Non-Graded Private Educational Institution: Input to an Enhanced Retention Strategies - Areola, PhD HSG, Eunice Mareth Querol; Domalaon, Pearliza Magkasi (Sekolah Tinggi Manajemen IPMI, 2023)
This study provides an analysis of teacher retention at a non-graded private educational institution in Quezon City, utilizing data from exit survey forms to departing teachers over the last three school years, starting from AY 2020-2021 to 2022-2023. The study focuses on the perceptions of departing employees regarding various factors that could influence teacher retention, grounded in Frederick Herzberg's Hygiene and Motivation factors. These identified factors hold the potential to assist the school in retaining proficient teachers by crafting a comprehensive rewards program, enhancing overall satisfaction levels, and deterring them from seeking employment elsewhere. The research methodology involves a descriptive study employing baseline data and the results of an exit survey instrument completed by seventy-two teachers who left during the past three academic years. The findings indicate that more than half of the turnover was due to voluntary resignations (56%), while (44)% were a result of management-initiated separations. Teachers' decisions to leave were generally driven by the accumulation of a number of factors. Among those who resigned, the primary reasons cited were the pursuit of better opportunities, improved work conditions, and higher compensation. Departing teachers generally expressed satisfaction with both motivation and hygiene factors, underscoring the need to make improvements in areas related to professional growth and development, as well as compensation and benefits. The findings suggest that a teacher's decision to stay is contingent on individual motivation, and the institution may consider designing a tailored retention strategy that integrates these insights into the five components of a total rewards program.